Book Review: ‘Metasex - The Discourse of Intimacy and Trangression’ (2020), by A. Storch and N. Nassenstein (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Storch and Nassenstein’s, Metasex - The Discourse of Intimacy and Trangression (2020) propose a holistic approach to the discursive strategies and cultural meanings around sexualities and metasex, namely the ‘metapragmatic discourses on sex’ (p. 1). Broadly defined, sex talk (sexting, jokes, seduction, etc.) is nowadays studied in prominently online settings in the West. However, its existence is transposed into face-to-face encounters in somewhat ‘staged’ and ‘embodied’ experiences in other parts of the world (p. 14). Using a pragmatic and ethnolinguistic lens, the book moves away from a sensationalist and etic interpretation of sexual discourses, materials, and consumerism by broadening the research scope and taking into account Southern and African perspectives that reveal the intricacies and multiple meanings of metasex and discourses of intimacy, transgression, and sensualization